Strategi Bertahan Hidup Perajin Gerabah Tradisional - Joan Hesti Gita Purwasih; Mahendra Wijaya; Drajat Tri Kartono (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
The decreased number of traditional earthenware craftsmen occurs due to three main factors: basic material, worker, and consumer. Some craftsmen instead prefer staying so that they should adapt to the existing condition. Nevertheless, in fact, some of them prefer stopping from being craftsmen now. Departing from this reality, the author tried to raise earthenware craftsmen’s adapting strategy to survive until today. The author employed a qualitative method. The phenomenological research was chosen with interview and observation being the techniques of collecting data. The result of research generally showed a variety of products produced aiming to document cultural heritage threatened to be extinct. Meanwhile, as the analysis technique, the author borrowed Julian Steward’s cultural-ecological perspective to explain the data found. Data analysis was conducted using an interactive technique of analysis. Considering the findings of the research, the craftsmen took a different surviving strategy today compared with that in the past. This change was effected by such constraints as basic material, consumer, and human resources. Julian Steward’s cultural-ecological concept seemed to be insufficient. Therefore, natural resources as the main basic material of industrial society should be understood more complexly to a more macro level.